Personality and error monitoring: an update - Hoffmann, Sven; Wascher, Edmund; Falkenstein, Michael (Frontiers in Human Neuroscience, 2012)
People differ considerably with respect to their ability to initiate and maintain cognitive control. A core control function is the processing and evaluation of errors from which we learn to prevent maladaptive behavior. People strongly differ in the degree of error processing, and how errors are interpreted and appraised. In the present study it was investigated whether a correlate of error monitoring, the error negativity (Ne or ERN), is related to personality factors. Therefore the EEG was measured continuously during a task which provoked errors, and the Ne was tested with respect to its relation to personality traits. Our results indicate a substantial trait-like relation of error processing and personality factors: The Ne was more pronounced for subjection scoring low on the “Openness” scale, the “Impulsiveness” scale and the “Emotionality” scale. Inversely, the Ne was less pronounced for subjects scoring low on the “Social Orientation” scale. The results implicate that personality traits related to emotional valences and rigidity are reflected in the way people monitor and adapt to erroneous actions.